Neutralizing antibody activity against the B.1.617.2 (delta) variant 8 months after two-dose vaccination with BNT162b2 in health care workers - Benning, Louise; Morath, Christian; Bartenschlager, Marie; Reineke, Marvin; Töllner, Maximilian; Nußhag, Christian; Kälble, Florian; Reichel, Paula; Schaier, Matthias; Klein, Katrin; Schnitzler, Paul; Zeier, Martin; et al. (Clinical microbiology and infection, 2022)
Objectives - Humoral immunity wanes over time after two-dose BNT162b2 vaccination. Emerging variants of concern, such as the B.1.617.2 (delta) variant, are increasingly responsible for breakthrough infections owing to their higher transmissibility and partial immune escape. Longitudinal data on neutralization against the B.1.617.2 (delta) variant are urgently needed to guide vaccination strategies. - Methods - In this prospective longitudinal observational study, anti-S1 IgG and surrogate neutralizing antibodies were measured in 234 collected samples from 60 health care workers after two-dose vaccination with BNT162b2 at five different time points over an 8-month period. In addition, antibodies against various severe acute respiratory syndrome coronavirus 2 epitopes, neutralization against wild-type, and cross-neutralization against the B.1.617.2 (delta) variant using a live virus assay were measured 6 weeks (second time point) and 8 months (last time point) after first vaccine dose. - Results - Median (interquartile range) anti-S1 IgG, surrogate neutralizing, and receptor-binding domain antibodies decreased significantly from a maximum level of 147 (102-298), 97 (96-98), and 20 159 (19 023-21 628) to 8 (4-13), 92 (80-96), and 15 324 (13 055-17 288) at the 8-month follow-up, respectively (p < 0.001 for all). Neutralization against the B.1.617.2 (delta) variant was detectable in all 36 (100%) participants at 6 weeks and in 50 of 53 (94%) participants 8 months after first vaccine dose. Median (interquartile) ID50 as determined by a live virus assay decreased from 160 (80-320) to 40 (20-40) (p < 0.001). - Discussion - Although humoral immunity wanes over time after two-dose BNT162b2 vaccination in healthy individuals, most individuals still had detectable neutralizing activity against the B.1.617.2 (delta) variant after 8 months.